Effect of Rabeprazole and Rebamipide in the Treatment of Upper Gastrointestinal Hemorrhage Associated with Dual Antiplatelet Therapy in Elderly Patients with Coronary Heart Disease. (November 2022) - Jia, Rong-Jie; Wang, Xiao-Peng; Zhang, Zhen-Hua; Cui, Hai-Hong; Qin, Rui; Du, Da-Yong; Liu, Yang
To investigate the therapeutic effect of rabeprazole and rebamipide on patient age over 60 with dual antiplatelet therapy (DAPT)–related upper gastrointestinal hemorrhage following percutaneous coronary intervention (PCI). A total of 360 patients age over 60 undergoing PCI were recruited for antiplatelet therapy involving a combined treatment of aspirin (100 mg/d) and clopidogrel (75 mg/d). The enrolled patients were divided into 4 groups: the control group, the rabeprazole group, the rebamipide group, and the rabeprazole + rebamipide group. The incidence and severity of any upper gastrointestinal hemorrhage and the incidence of major adverse cardiac events (MACEs) were observed 6 months after the operation. The incidence of upper gastrointestinal hemorrhage in the 4 groups was 11.1%, 3.3%, 8.9%, and 1.1%, respectively, and the differences were statistically significant ( P  < 0.05). On comparing the groups, the differences between the control group and the rabeprazole group, those between the control group and the rabeprazole + rebamipide group, and those between the rebamipide group and the rabeprazole + rebamipide group were found to be statistically significant ( P  < 0.05). The severity of the upper gastrointestinal hemorrhage in the rabeprazole group and the rabeprazole + rebamipide group was significantly lower than that in the control group. The 4 groups exhibited no significant differences in the incidence of MACEs ( P  > 0.05). For patients age over 60 receiving DAPT following PCI in our study population, treatment with rabeprazole or a combination of rabeprazole and rebamipide could reduce the risk of upper gastrointestinal hemorrhage, as well as reduce its severity.